ANALISIS PERAWATAN DEWI-DEWI SEKOCI UNTUK MENCEGAH HAMBATAN PENURUNAN SEKOCI DI KMP TITIAN NUSANTARA - Tiara Tesya; Kurniawan Abadi; Rizal Rochmansyah; Nelfi Erlinda; I Kadek Laju (UNIMAR AMNI Semarang, 2026)
This study aims to analyze the maintenance system of lifeboat davits in preventing obstacles during the launching process of lifeboats on board KMP Titian Nusantara. Lifeboat davits are important safety equipment used to lower lifeboats during emergency situations at sea. This research uses a qualitative descriptive method with data collection techniques including observation, interviews, and documentation conducted directly on board the vessel. The results show that the maintenance of lifeboat davits has not been carried out optimally. Several problems were found, such as pulley jams, corrosion on components, and lack of lubrication on moving parts. These problems can potentially hinder the lifeboat launching process during emergency conditions. Therefore, routine inspection, proper maintenance procedures, and increased crew awareness are necessary to ensure the readiness of lifeboat davits. Proper maintenance management will improve the reliability of safety equipment and support maritime safety operations.